Dual-axis hormonal covariation in adolescence and the moderating influence of prior trauma and aversive maternal parenting - Simmons, Julian; Byrne, Michelle L.; Schwartz, Orli S.; Whittle, Sarah L.; Sheeber, Lisa; Kaess, Michael; Youssef, George J.; Allen, Nicholas B. (Developmental psychobiology, 2015)
Adversity early in life can disrupt the functioning of the hypothalamic-pituitary-adrenal and hypothalamic-pituitary-gonadal axes and increase risk for negative health outcomes. The interplay between these axes and the environment is complex, and understanding needs to be advanced by the investigation of the multiple hormonal relationships underlying these processes. The current study examined basal hormonal associations between morning levels of cortisol, testosterone, and dehydroepiandrosterone in a cohort of adolescents (mean age 15.56 years). The moderating influence of childhood adversity was also examined, as indexed by self-reported trauma (at mean age 14.91), and observed maternal aggressive parenting (at mean age 12.41). Between-person regressions revealed significant associations between hormones that were moderated by both measures of adversity. In females, all hormones positively covaried, but also interacted with adversity, such that positive covariation was typically only present when levels of trauma and/or aggressive parenting were low. In males, hormonal associations and interactions were less evident; however, interactions were detected for cortisol-testosterone — positively covarying at high levels of aggressive parenting but negatively covarying at low levels — and DHEA-cortisol — similarly positively covarying at high levels of parental aggression. These results demonstrate associations between adrenal and gonadal hormones and the moderating role of adversity, which is likely driven by feedback mechanisms, or cross-talk, between the axes. These findings suggest that hormonal changes may be the pathway through which early life adversity alters physiology and increases health risks, but does so differentially in the sexes; however further study is necessary to establish causation. © 2015 Wiley Periodicals, Inc. Dev Psychobiol 57: 670-687, 2015.
Gesehen am 17.06.2020